Perlindungan Hukum terhadap Kebebasan Beragama di Indonesia: Analisis Kasus Gereja Kristen Indonesia (GKI) Yasmin dan Kegagalan Implementasi Putusan Pengadilan - Mercy Natania; Ni Made Witari Dewi (Green Publisher Indonesia, 2026)
This study analyzes the legal protection of religious freedom in Indonesia through the case of the GKI Yasmin Church, with a focus on the failure to implement court decisions. Although Indonesia is constitutionally recognized as a state based on the rule of law, the enforcement of final and binding judicial decisions often encounters obstacles in practice. This research aims to examine the gap between legal norms and their implementation, particularly in the protection of religious freedom. The study employs a normative juridical method with a qualitative approach, relying on legislation and court decisions as primary sources. The findings reveal that despite clear rulings in favor of GKI Yasmin, local authorities failed to comply, indicating weak law enforcement and the influence of non-legal factors such as social pressure and political considerations. This condition reflects a broader structural problem in the enforcement of law and undermines judicial authority, thereby weakening the protection of fundamental human rights. Furthermore, the failure to implement court decisions highlights the inconsistency between legal norms and their application in practice. The study concludes that stronger state commitment, improved supervision, and effective enforcement mechanisms are essential to ensure the protection of religious freedom and uphold the rule of law in Indonesia